2021
DOI: 10.26905/pjiap.v6i1.5514
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh inventarisasi aset, penggunaan aset, pengamanan dan pemeliharaan aset terhadap optimalisasi aset tetap tanah pada pemerintah Kabupaten Malang

Abstract: In the era of national transformation and regional autonomy, there have been many breakthroughs in the management of land fixed assets, but many financial problems and land assets have not been implemented optimally, effectively and efficiently in their management. This study was used to analyze the effect of asset management on the optimization of fixed land assets in Malang Regency Government. The independent variables used in this study were asset inventory, asset use, asset security, and maintenance, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
1
0
8
Order By: Relevance
“…The results of this research are in line with previous research, which found that regional asset management carried out optimally by paying attention to the principles of efficiency, effectiveness, transparency, and public accountability has a positive impact on the orderly administration of regional assets, efficiency, and effectiveness in the use of regional assets, safeguarding regional assets, and availability of accurate and up-to-date information regarding regional assets (Wicaksana et al, 2021). Subsequent research also found that optimal management and utilization of regional assets can trigger regional economic growth (Santoso et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this research are in line with previous research, which found that regional asset management carried out optimally by paying attention to the principles of efficiency, effectiveness, transparency, and public accountability has a positive impact on the orderly administration of regional assets, efficiency, and effectiveness in the use of regional assets, safeguarding regional assets, and availability of accurate and up-to-date information regarding regional assets (Wicaksana et al, 2021). Subsequent research also found that optimal management and utilization of regional assets can trigger regional economic growth (Santoso et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…A firm or government organisation must compile an asset inventory to determine their assets' number and condition. [14]…”
Section: Monitoringmentioning
confidence: 99%
“…Berbagai alat dan fasilitas yang digunakan oleh pihak mitra sebagian masih bersifat pemakaian bersama dengan pihak pemerintah desa. Pihak mitra menyatakan bahwa dengan kondisi seperti itu sulit mengukur keuntungan dan kerugian serta perkembangan usaha (Wicaksana et al, 2021). Dalam upaya mematuhi peraturan perundangan tentang lembaga sektor publik, pemerintah desa dan perwakilan masyarakat sudah sejak tahun 2019 meminta laporan perkembangan BUMDes secara periodik sekurang-kurangnya dua kali dalam satu tahun.…”
Section: Gambar 1 Ruang Operasional Usaha Milik Mitra Pengabdianunclassified
“…Pelaksanaan kegiatan dilakukan selama empat bulan, sejak observasi lapangan pada bulan Januari tahun 2021 sampai dengan selesai pendampingan pada bulan Mei 2021, melibatkan para pemangku kepentingan yang memiliki peran kunci dalam pengelolaan mitra. Kegiatan awal, yaitu observasi dilakukan dua kali pada minggu pertama dan mendapatkan data sebagai berikut: (1) Lokasi pihak mitra berada satu kompleks dengan kantor balaidesa, sehingga memungkinkan terjadi kesulitan menilai aset yang terkait dengan pemakaian bersama antara mitra dan pemerintah desa (Wicaksana et al, 2021). (2) Sejak awal beroperasi, pihak mitra tidak memiliki daftar identifikasi barang yang diperjualbelikan sehingga menyulitkan pencatatan transaksi terkait pengelolaan keuangan (Chandra, 2016).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation